An Attempt at Estimation of Sexual Dimorphism of Selected Morphological Characters of Human Fetuses - Borysławski, Krzysztof; Kurlej, Wiesław (Anthropological Review, 1983)
On the material comprising 162 male and 173 female fetuses of various ages the authors observe. sexual dimorphism of the following metric characters: total body length, crown-rump length, body weight, 4 head dimensions and 6 dimensions of the palate. The data was standarized in four-day age intervals by a procedure based on Lagrange's formula. Results of the present study point toward a cyclic change of the growth velocity of fetuses with respect to sex.